THE ROLE OF VIDEO-BASED INSTRUCTION IN FOREIGN LANGUAGE ACQUISITION: PEDAGOGICAL IMPLICATIONS AND EFFECTIVENESS (Web of Teachers: Inderscience Research, 2025)
The integration of video-based instruction in foreign language education has gained significant attention due to its potential to enhance linguistic competence and cultural awareness. This study explores the pedagogical implications of utilizing video materials in language learning, emphasizing their role in improving listening comprehension, vocabulary acquisition, and communicative skills. By analyzing empirical research and case studies, the paper examines how videos provide authentic language exposure, facilitate contextual learning, and increase learner engagement. Additionally, the study discusses the effectiveness of various video formats, including instructional videos, films, and multimedia resources, in fostering an immersive learning environment. The findings highlight the benefits and challenges associated with video-assisted language instruction, offering insights into best practices for educators.